Coplanar waveguide resonator using PLZT thin film. (27th July 2017) - Gupta, Reema; Rana, Lokesh; Sharma, Anjali; Freundorfer, A. P.; Sayer, Michael; Tomar, Monika; Gupta, Vinay
ABSTRACT: A coplanar waveguide (CPW) resonator has been fabricated on a silicon substrate using PLZT thin film. The fabricated CPW resonator provides various advantages as compared to stripline and microstrip resonators in terms of transmission and size reduction. The PLZT thin film has been deposited using pulsed laser deposition technique under optimized growth parameters and the CPW resonator has been fabricated using the conventional photolithography technique. The PLZT based CPW resonator was found to resonate at 13.9 GHz frequency which is advantageous for K-B and communication.